A Reply to "A Comment on 'Accounting Method Choice in the Software Industry''. - Trombley, Mark A. (The Accounting Review, 1990)
Presents the author's reply to the comments of Paul F. Williams et al on the 1989 article `Accounting Method Choice in the Software Industry,' in the October 1990 issue of `The Accounting Review.' Sample characteristics; Auditor preference and accounting choice; Size and accounting choice.